Accident analysis of the Gumi hydrogen fluoride gas leak using CFD and comparison with post-accidental environmental impacts. (July 2017) - Yang, Seeyub; Jeon, Kyeongwoo; Kang, Dongju; Han, Chonghun
Abstract: This work uses computational fluid dynamics (CFD) to model the disastrous Gumi hydrogen fluoride gas leak of 2012. To ensure the model's validity, an anhydrous hydrogen fluoride leak field test was validated using a single-phase and two-phase dispersion model, and then compared with other dispersion models. When combined with the anhydrous ammonia leak test, the overall mean relative bias is 0.135 and mean relative square error is 0.068, which is within the valid range for dispersion simulation. The Gumi hydrogen fluoride gas leak disaster is then simulated and compared with the actual impacts. Human fatality occurred only in the plant and probability of death via toxic exposure shows a similar result. Toxic dose measurement by post-accidental vegetation fluoride concentration shows a similar range with CFD results for the downwind side. Highlights: Anhydrous hydrogen fluoride field test is validated using CFD. Hydrogen fluoride gas leak in 2012 is simulated using CFD. CFD result is compared with human fatality and environmental impacts.